2001
DOI: 10.1007/s00259-001-0695-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body biodistribution, radiation absorbed dose, and brain SPET imaging with [123I]5-I-A-85380 in healthy human subjects

Abstract: The biodistribution of radioactivity after the administration of a new tracer for alpha4beta2 nicotinic acetylcholine receptors (nAChRs), [123I]5-iodo-3-[2(S)-2-azetidinylmethoxy]pyridine (5-I-A-85380), was studied in ten healthy human subjects. Following administration of 98+/-6 MBq [123I]5-I-A-85380, serial whole-body images were acquired over 24 h and corrected for attenuation. One to four brain single-photon emission tomography (SPET) images were also acquired between 2.5 and 24 h. Estimates of radiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 11 publications
4
40
1
Order By: Relevance
“…Studies of non-human primates and humans have examined distributions of nAChRs with these new tracers, and found regional densities of these receptors similar to those in the animal work cited above (Chefer et al, 1999Fujita et al, 2002;Fujita et al, 2003;Kimes et al, 2003;Valette et al, 1999). In initial human studies, no subjective or cardiovascular effects of 2-FA have been reported; however, studies of tobacco dependent subjects have not yet been published.…”
Section: Functional Imaging Of Nicotinic Acetylcholine Receptorsmentioning
confidence: 64%
“…Studies of non-human primates and humans have examined distributions of nAChRs with these new tracers, and found regional densities of these receptors similar to those in the animal work cited above (Chefer et al, 1999Fujita et al, 2002;Fujita et al, 2003;Kimes et al, 2003;Valette et al, 1999). In initial human studies, no subjective or cardiovascular effects of 2-FA have been reported; however, studies of tobacco dependent subjects have not yet been published.…”
Section: Functional Imaging Of Nicotinic Acetylcholine Receptorsmentioning
confidence: 64%
“…To extend our knowledge concerning the nAChR subtypes in monkey striatum and the effect of nigrostriatal damage on receptor expression, we performed quantitative autoradiography in control and parkinsonian monkey brain using 5 (Sullivan et al, 1996;Villemange et al, 1998;Mukhin et al, 2000;Fujita et al, 2002), although more recent work indicates it may also bind to ␣6* nAChRs (Kulak et al, 2002b). In the present study we examine the effect of ␣-conotoxin MII on binding of [ 125 I]A-85380 to ␤2*-containing nicotinic receptors and extend previous work elucidating the nAChR subtypes affected by nigrostriatal damage in the primate striatum.…”
Section: Atal [mentioning
confidence: 99%
“…Iodine-123-5-IA-85380 ([ 123 I]5-IA; [ 123 I]-5-iodo-3-[2(S)-2-azetidinylmethoxy] pyridine) demonstrates many of the properties necessary for in vivo imaging of β 2 -nAChR with SPECT including high affinity (K D =11 pM), rapid entry into brain, low nonspecific binding, and minimal toxicity [9,10]. The pharmacological specificity of [ 123 I]5-IA for β 2 -nAChRs has been confirmed by the lack of binding in brain of β 2 (-/-) knockout mice [24].…”
Section: Introductionmentioning
confidence: 99%